Trajano en la literatura de corte de Teodosio y Justiniano - Guillermo González del Campo (Talia dixit, 2009)
This article intends to clarify the meaning of the mentions of Trajan in texts written by authors close to the emperors Theodosius and Justinian. Issues involved go from the panegyric to the rejection of the pagan past. The analysis will lead to explore also some of the specific methods used by these authors in order to flatter their addressees.